Fiber optic displacement sensor based on concave mirror - Harun, Sulaiman Wadi; Yang, Hang Zhou; Lim, Kok Sing; Tamjis, Mohamad Rom; Dimyati, Kaharudin; Ahmad, Harith (National Institute of Optoelectronics, 2009)
Fiber optic displacement sensor (FODS) is proposed using a concave mirror for enhanced flexibility in sensitivity selection and linear range. The displacement measurement up to 26mm can be achieved using 12mm focal length. The second dip of the displacement response is located at distance equivalent to twice of focal length. The experimental results show that the sensitivity and the linear range of the sensor are strongly dependent on the focal length of the mirror. With a focal length of 12mm, the maximum sensitivity of 0.299, the longest linear range of 3.5mm is obtained at the 3rd and 2nd slope, respectively.